POPULASI TARSIUS (Chephalopacus bancanus) DI HUTAN SEKUNDER DUSUN AMAWANGK DESA RE"™ES KECAMATAN MENJALIN KABUPATEN LANDAK - Pongkot, Arianto; Anwari, M Sofwan; Riyono, Joko Nugroho (JURNAL HUTAN LESTARI, 2024)
Tarsiers are one of the endemic animals of Kalimantan that are protected by their existence, tarsiers live in primary forests and secondary forests and can be in the middle between primary forests and secondary forests in the hamlet of Amawangk. This study aims to examine the tarsier population (Chephalopacus bancanus) in the forest of Amawangk Hamlet, Re'es Village of West Kalimantan Hedgehog Regency. Data collection technique is carried out by observing tarsier populations by sampling a combination of line transect and concentration count methods, the results of the study showed that tarsiers live in groups between 2-6 individuals, with population densities in the forest area of amawangk hamlet obtained during the study of 2 individuals / ha or 20 individuals / km ². Tarsiers' habitats at the research site include secondary and primary forests.Keywords: Amawangk Hamlet, Primary Forests and Secondary Forests, Tarsius Population.AbstrakTarsius merupakan salah satu hewan endemik Kalimantan yang dilindungi keberadaannya, tarsius hidup di hutan primer maupun hutan sekunder dan bisa berada di tengah-tengah antara hutan primer dan hutan sekunder di dusun Amawangk. Penelitian ini bertujuan untuk mengkaji populasi tarsius (Chephalopacus bancanus) yang ada hutan Dusun Amawangk, Desa Re"™es Kabupaten Landak Kalimantan Barat. Teknik penggumpulan data dilakukan dengan pengamatan populasi tarsius dengan cara perpaduan antara metode line transect dan concentration count, hasil penelitian menunjukan bahwa tarsius hidup berkelompok antara 2-6 individu, dengan kepadatan populasi di kawasan hutan Dusun Amawangk yang diperoleh selama penelitian sebesar 2 individu/ha atau 20 individu/km ². Habitat tarsius pada lokasi penelitian mencakup hutan sekunder dan hutan primer. Kata kunci: Dusun Amawangk, Hutan Primer dan Hutan Sekunder, Populasi Tarsius